Synthesis, characterization and thermal behaviour of solid 4-methoxybenzoates of heavier trivalent lanthanides - Rodrigues, Emanuel C.; Siqueira, Adriano B.; Ionashiro, Elias Y.; Bannach, Gilbert; Ionashiro, Massao [UNESP] (Elsevier B.V., 2006)
Solid-state Ln-4-MeO-Bz compounds, where Ln stands for trivalent Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu and Y and 4-MeO-Bz is 4-methoxybenzoate, have been synthesized. Simultaneous thermogravimetry and differential thermal analysis (TG-DTA), differential scanning calorimetry (DSC), X-ray powder diffractometry, infrared spectroscopy and complexometry were used to characterize and to study the thermal behaviour of these compounds. The results led to information about the composition, dehydration, phase transition, coordination mode, structure, thermal behaviour and thermal decomposition of the isolated compounds. The phase transition observed in the some compounds has been reported for the first time. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: heavier lanthanides; 4-methoxybenzoate; characterization; thermal behaviour